PATRIARCHY BEHIND KIM JI-YOUNG, BORN 1982: A BIOGRAPHICAL APPROACH - Chatarini Septi Ngudi Lestari; Yulita Andini Putri Baruna (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2022)
This study reveals the patriarchal culture experienced by Kim Ji-Young as the main character in a novel titled Kim Ji-Young, Born 1982 by Cho Nam-Joo. This study aims to discover the structures of the patriarchal culture experienced by Kim Ji-Young and their impacts on her life. A biographical approach is employed to relate the author’s life and thoughts to her work. Data are analyzed qualitatively by classifying the structures of patriarchal culture under Sylvia Walby’s theory and describing their impacts by Irish Marion Young’s theory of gender oppression. The results show six patriarchal cultural structures that Kim Ji-Young experienced since childhood. In her childhood, Kim Ji-Young experienced discrimination in culture, violence, and the state system. In her adolescence, she encountered unequal treatment in culture and sexuality. Growing up, she suffered from the gender pay gap, household production, sexuality, culture, and violence. Patriarchal culture has impacted her life in four aspects, violence in her adolescence and adulthood, powerlessness during childhood and adulthood, marginalization during childhood and adulthood, and exploitation in her adulthood. The results concluded that Kim Ji-Young experiences patriarchal culture, which significantly influences her life. Interestingly, the novel Kim Ji-Young, Born 1982, reflects the biography of Cho Nam-Joo. Therefore, the patriarchal experience of Cho is reflected in the character of Kim Ji-Young in the novel.